Pengaruh Sanksi Pajak, Pengetahuan Perpajakan, dan Transparansi Laporan Keuangan Terhadap Kepatuhan Wajib Pajak Koperasi Wanita Kecamatan Mojosari Periode 2019-2023 - Indah Dewi Sekar Ayu; Nur Ainiyah; Nurdiana Fitri Isnaini (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
This research aims to examine the influence of tax sanctions, tax knowledge, and transparency of financial reports on taxpayer compliance in women's cooperatives. This research is quantitative in type. The population in this study was the Mojosari District women's cooperative for the 2019-2023 period, totaling 20. The sampling technique used the purposive sampling method so that 14 respondents were obtained. This research uses primary data obtained from distributing questionnaires via Google form with a measuring tool in the form of a Likert scale. The data analysis technique uses descriptive statistics with the SmartPLS data testing tool using outer model and inner model measurement models. The research results show that tax sanctions, tax knowledge have a positive and significant effect on taxpayer compliance, while financial report transparency has no effect on taxpayer compliance.